NASIONALISME DAN KEISLAMAN UNIVERSAL DALAM NOVEL MAWAKK IB AL-AHRR ARR KARYA NAJIB KYLANI - Yulia Nasrul Latifi (IBDA` : Jurnal Kajian Islam dan Budaya, 2015)
This article discusses an Egypt modern novel of Najib al-Kylani,Mawakib al-Ahrar, which tells about the struggle of Egyptians to get their independence from French colonization. One interesting point of this novel is the idea of critical and progressive nationalism. In contrast, postcolonial theory is focused on the aspects of nationalism using deconstruction methods. This theory is based on Edward Said argument on ‘East’ discourse through its orientalism as a product of science that has ideological basis and colonial interests. Their political and economic colonialism is accompanied by cultural colonialism through representing the East as ‘The Other’. Said developed his theory by using Foucault’s power concept and developed Derrida’s binary opposition. The progressive idea of this novel has a closed relationship with the universal values of Islam, characterized by inclusivity, egalitarianism, and democracy. Theologically and historically, Islam has taught the unity of human being and the need of plurality and differences of human beings, cultures, and nations to compete in good manner. Dialogical and mutual understanding of cultures is really important, not the exception between the West and the East cultures. Tulisan ini membahas novel modern Mesir yang berjudul Mawakib al-Ahrar karya Najib al-Kylani. Novel ini mengisahkan tentang perjuangan rakyat Mesir untuk mendapatkan kemerdekaan selama dalam penjajahanPerancis. Yang menarik dari novel ini adalah gagasan nasionalisme yang sangat kritis dan progresif. Sementara itu, teori poskolonial yang difokuskan pada aspek nasionalisme dengan memakai metode dekonstuksi. Teori ini didasarkan pada gugatan Edward Said tentang wacana ‘Timur’ melalui orientalismenya sebagai produksi ilmu pengetahuan yang memiliki landasan-landasan ideologis dan kepentingan-kepentingan kolonial. Penjajahan politik dan ekonomi mereka disertai pula penjajahan kultural berupa representasi Timur sebagai ‘Sang Lain’. Said mengembangkan teorinya dengan memakai konsep kekuasaan Foucault dan mengembangkangagasan oposisi biner Derrida. Gagasan novel yang progresif inimemiliki keterkaitan erat dengan nilai-nilai keislaman universal yang bercirikan inklusif, egaliter, dan demokratis. Secara teologis ataupun historis, Islam telah mengajarkan kesatuan manusia dan pentingnya pluralitas dan perbedaan manusia, budaya, dan bangsa untuk berlomba-lomba dalam kebaikan. Pemahaman budaya secara dialogis dan mutualistik sangat penting, termasuk budaya yang dialogis antara Barat dan Timur.